EXPRESSIONS OF MASONIC BOOK CULTURE IN LITHUANIA IN THE 19TH CENTURY - Pacevičius, Arvydas (Knygotyra, 2016)
The article investigates the expression of Masonic book culture in Lithuania, viewed as the lands of the former Grand Duchy of Lithuania, in the 19th century. This culture is recognizable from the special symbols and bibliographic design. The article also researches such activities of Freemasons, active in Lithuania since 1776, as storage and distribution of collections owned by them, book publishing, symbolism of illustrations and cover page structure. The very term Masonic book is used to describe the books compiled, stored and used by members of this Masonic Brotherhood as well as the books related to Freemasons. It has been established that at the beginning of the 19 century, side by side with the personal collections held by Michał Dłuski, Kazimierz Kontrym and Johann Friedrich Wolfgang, the Masons also collected the libraries of the Gorliwy Litwin, Reformed Gorliwy Litwin and other Lodges. Proof of that has been found in the surviving Vilnius University Gift Book, 1792–1832, a list of books acquired by the Vilnius Lodge Gorliwy Litwin, signed by Michał Dłuski on October 23, 1816 as well as archival sources. The main incentive to collect books was storage of the Brotherhood memory, self-education, moral development, training Brotherhood discipleship, and preparation of ritual statements. The illustrations of the Masons’ books, particularly their title pages and comments in their ritual works reflect the same instruments as the ones used in the portraits of Lithuanian Masons such as a hammer, a plumb, a level, a square, a compass, a trowel, etc. One can also find other generalized symbols of the Age of Enlightenment and Freemasonry in these books such as the eye of providence, a sword, an hourglass, a skull, a punch, etc. The books also stand out from the rest in their unusual structure of bibliographic design (Mason-specific marking of the year of publication and provenance, encryption of the lodge name, etc.) Even though Masons in Lithuania were not actively involved in publishing activities, they commissioned the publication of subject-specific brochures and various forms from the bookmen Jozef Zawadzki and Christian Weise. In the sphere of publishing and distribution, Freemasons collaborated with the Tilsit Masonic lodge ‘Louise under the Open Hearts’, functioning from 1799 to 1835. In this context, the donation of ‘Lithuanian Bible Histories’ by Ludwig Rhesa (1816) on August 27, 1817, could be regarded as a manifestation of not only ethnic but Masonic relationship as well. Ludwig Rhesa, professor of the Konigsberg university, was from 1806 member of the Konigsberg Masonic lodge ‘Three Crowns’; in the period 1816–1819, he served as orator. After the persecution instigated against Freemasons by Emperor Alexander’s administration started in 1812, they gave over to Vilnius university library the books of 26 titles – in total, 28 volumes (on February 20, 1824 and May 7, 1824, respectively). Three more Masonic books, used during the rituals conducted, have been identified on the basis of historiographic sources. The majority of books were aimed at Masonic lawmaking, rituals, history as well as philosophical issues of Freemasons. The books collected were in French, German, Polish, Latin and Russian languages. After the closure of Vilnius University in 1832, a major part of Masonic books were taken to Kiev. In the mid 20th century, however, thanks to prof. Levas Vladimirovas’ efforts, they were returned to the Vilnius University library storage. The surviving Masonic books reflect Freemasons’ symbolic thinking, their moral values as well as a transnational nature of the Brotherhood activities. On the other hand, the surviving books, their design and binding were related not only to the elite book and luxury but also to mid layer of town-dwellers‘and the intelligentsia, which was beginning to develop. The functioning of the Masonic book culture from a broader perspective of both space and time could be revealed by further studies.
Keywords: ...